1983
DOI: 10.1016/0035-9203(83)90103-7
|View full text |Cite
|
Sign up to set email alerts
|

The adverse consequences of heavy Trichuris infection

Abstract: Sixty-seven children with heavy Trichuris trichiura infection (Group A) were compared to 73 control children of similar socio-economic status but with light or no T. trichiura (Group B), for nutritional status, rates of concomitant bacterial and protozoal, and symptoms and clinical signs associated with heavy T. trichiura infection. Anoscopy was used to determine heavy T. trichiura infection. Measurements and physical examination were done on Group A on admission to and discharge from hospital; 46% were seen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Additionally, we have found that even when controlled for nutritional status, early childhood cryptosporidial infection either with or without diarrhea was associated with reduced fitness at 6–9 years of age and retarded weight gain [37]. Also, similar to the cognitive deficits seen in infestation with STHs [38], Giardia has been associated with decreased cognitive performance [39][41]. The overall impact of even “asymptomatic" disease from enteric protozoa, therefore, may be a major contributor to lost human potential.…”
Section: The Nep Belong With the Sths As Stunting Pathogensmentioning
confidence: 82%
“…Additionally, we have found that even when controlled for nutritional status, early childhood cryptosporidial infection either with or without diarrhea was associated with reduced fitness at 6–9 years of age and retarded weight gain [37]. Also, similar to the cognitive deficits seen in infestation with STHs [38], Giardia has been associated with decreased cognitive performance [39][41]. The overall impact of even “asymptomatic" disease from enteric protozoa, therefore, may be a major contributor to lost human potential.…”
Section: The Nep Belong With the Sths As Stunting Pathogensmentioning
confidence: 82%
“…In these children, 39% of the variance in plasma proteins was explained by plasma levels of fibrinogen and total globulin. A low mean SA was reported by Gilman et al 15 In the complete blood count (CBC) there is a microcytic iron deficiency anemia and a nonspecific leukocytosis in TDS. 3 The objectives of this study were to explore 1) the relationship between plasma IGF-1 and other markers of growth; and 2) the effect of serum concentrations of TNF on growth variables in children (2-10 years) stunted by TDS, recovering cases, and their unaffected matched controls.…”
mentioning
confidence: 86%
“…Trichuriasis is widespread in Nigeria and has been reported by Okpala (1961) and Holland et al (1989). The parasite causes rectal prolapse, anaemia, finger clubbing and retarded growth in man (Jung and Beaver 1951;Bowie et al, 1978 andGilman et al 1983). Weight loss and formation of nodules in the caecal wall which leads to diarrhea and anorexia in pigs.…”
Section: Gastrointestinal Helminth Parasitesmentioning
confidence: 99%